Enabling open-ended questions in team-based learning using automated marking: impact on student achievement, learning and engagement - Tan, Sophia Huey Shan (2022)
Background: Different types of assessments influence learning and learning behaviour. Multiple-choice questions (MCQs) reward partial knowledge and encourage surface learning, while open-ended questions (OEQs) promote deeper learning. Currently, MCQs is part of team-based learning (TBL) curriculum, and it is challenging to implement OEQs as immediate feedback is necessary. Objectives: We asked if MCQ and OEQs affect student achievement, student learning and student engagement differently in a TBL classroom. Methods: MCQs and OEQs test scores of N = 66 students were automatically captured in Learning Activity Management System (LAMS) and were compared using a switching replications quasi-experimental design with pre- and post-tests to answer the research questions. Student learning approaches and engagement in the team activities were assessed using the study process questionnaire and the structure of observed learning outcomes taxonomy respectively. Results and Conclusions: Students get significantly higher MCQ scores than OEQs for the same set of questions, but the reverse is true for application exercises (AEs), which focus on higher-level application. Most students significantly deepened their learning approaches before OEQs, while poorly prepared students were less engaged during OEQ discussions. Interestingly students subjected to OEQs took less time and scored higher in AE discussions, suggesting better focus on higher-level thinking. Implications: This project is significant as it bridges our understanding of the value of OEQs and TBL. Our approach is transferable to other courses, and thus it can improve the quality of teaching and learning in tertiary education.